Produção textual: o que dizem e escrevem educandos do 3ª ano sobre o gênero fábula - Cunha, Alessandra Marques da (2010)
The present research aimed at verifying and analyzing what 9-year-old pupils from the third year of primary school used to write and say about writing production and fables, as well as the knowledge they claimed and demonstrated to have learned on writing and orality through mediations and dialogues between the educator, the pupils and the researcher. Concepts such as language, orality, reading, writing, genre, project and didactic sequence served as guidance to the research and were evidenced within a socio-historical approach based on the studies and works by Bakhtin, Vygotsky and their developments glimpsed in the current researches in the education and language fields, especially represented in the works by the Genebra Group researchers (Dolz, Schneuwly, Pasquier and Bronckart). The methodology used was the dialogic-collaborative one, since we understand that such a proposal was the best way of carrying out a study in which the participants are able to work in exchange conditions, in addition to allowing the introduction of a culture moved by common goals of transforming the school daily routine through dialogue. The data, which served as reference to our considerations, were collected during the attendance to a 60-hour course offered by the Federal University of São Carlos and aimed at first-to-fourth-year primary educators of a Municipal School. Such a course intended to provoke reflections based on readings, discussions, analyses of textual productions and work situations in the classroom with the textual production theme along with the pupils. The data obtained through this study indicated that, in the first stage of data collection, the pupils concerns focused primarily on aspects related to the writing acquisition system, which was evidenced by, for instance, their effort to getting to know the letters, the order of the letters, the correct spelling, among others, rather than on aspects related to textual production. Even though rewriting presented elements which contemplated characteristics of the fables (genre adopted in our research as the axle to the considerations), such characteristics did not appear in the pupils speeches, which therefore did not allow comparison criteria. It was observed that, in the first stage of data collection, they used to do their classroom tasks without asking the whys, consequently generating an activity more directed to filling in time rather than constructing knowledge. However, after the mediations provided by the research between educator - pupils, pupils - pupils and pupils researcher, the data indicated that the teaching and learning situations based on dialogue strengthened the arguments and counter-arguments of the pupils, thus helping them to better elaborate and construct their thoughts and linguistically structure sentences. Turning the pupils into protagonists of their learning processes also made them co-responsible and aware of their knowledge acquisition process, because this way they had very clearly defined what they should know by the end of the didactic sequence. The collected data also signalized that the instruments and support material selected by the educator are also mediators of the pupils knowledge; therefore, the choices each educator makes also imply the pupils learning. By the end of the process, the pupils demonstrated acquisition of the characteristics of the genre fables, both orally and in writing, which proves that the work developed with textual production, focused on genre and organized based on didactic sequences, supported the pupils learning. We also noted that reading, retelling, rewriting and collective reviews should be stimulated and worked on since kindergarten in order to provide pupils with tools they can use to become competent readers and writers in the long run.